An assessment of students' entrepreneurial skills and characteristics and the impact on their entrepreneurial intention: a case of maharat applied science centers - Gholamhossein Hosseininia; Pouria Ataie; Ahmad Yaghoubi Farani (آموزش مهندسی ایران, 2017)
The main purpose of this survey study was to assess students’ entrepreneurial skills and characteristics in Maharat Applied Science Centers and its impact on their entrepreneurial intention. The research population was all students of Maharat Applied Science Centers (Approximately 21000 students). Samples of 377 students were selected through stratified random sampling (Krejcie and Morgans’ table was used for estimating research sample). Data was collected using a researcher made questionnaire. Research variables were entrepreneurial skills (Knowledge about business plan, communication, and familiarity with the legal and commercial rules, planning, team building and marketing), entrepreneurial characteristics and entrepreneurial intention. Questionnaires’ face validity was confirmed by a panel of experts and pilot test was performed to evaluate its reliability that Cronbach's alpha was 0.96. For analyzing data, coefficient of variation, one sample t-test, Pearson coefficient and multiple linear regression were used. Findings indicated that three skills such as planning, team building and familiarity with the legal and commercial rules had been significant difference with average scale (Respectively 12, 15 and 9). As well as, four factors like achievement motivation, challenge-taking, marketing and action-taking could be explain 56 percent of changes in dependent variable (students’ entrepreneurial intention). In other words, the four variables are predicted 56 percent of students' entrepreneurial intention and another 44 percent are predicted by other variables. At the end, according to the results, applicable recommendations were presented.